Caenorhabditis Elegans Exhibits Morphine Addiction-like Behavior via the Opioid-like Receptor NPR-17 - Ide, Soichiro; Kunitomo, Hirofumi; Iino, Yuichi; Ikeda, Kazutaka (Frontiers in Pharmacology, 2022)
Addiction has become a profound societal problem worldwide, and few effective treatments are available. The nematode Caenorhabditis elegans (C. elegans) is an excellent invertebrate model to study neurobiological disease states. C. elegans reportedly developed a preference for cues that had previously been paired with addictive drugs, similar to place conditioning findings in rodents. Moreover, several recent studies discovered and reported the existence of an opioid-like system in C. elegans. Still unclear, however, is whether C. elegans exhibits addictive-like behaviors for opioids, such as morphine. In the present study, we found that C. elegans exhibited dose-dependent preference for morphine using the conditioned chemosensory-cue preference (CCP) test. This preference was blocked by co-treatment with the opioid receptor antagonist naloxone. C. elegans also exhibited aversion to naloxone-precipitated withdrawal from chronic morphine exposure. The expression of morphine-induced CCP and morphine withdrawal were abolished in worms that lacked the opioid-like receptor NPR-17. Dopamine-deficient mutant (cat-2 (e1112)) worms also did not exhibit morphine-induced CCP. These results indicate that the addictive function of the opioid system exists in C. elegans, which may serve as a useful model of opioid addiction.